ANALISIS KANDUNGAN POLIFENOL DALAM RUMPUT LAUT Eucheuma sp DENGAN METODE SPEKTROFOTOMETRI UV-VISIBLE - Rachmat Kosman; Pirman AP; Sukmawati Syarif (As-Syifaa Jurnal Farmasi, 2009)
Seaweed are one of resource foreign exchange of state and earning source for coastal area society. Besides can be used direct upon which food, some result processing of seaweed like gelatinous, carrageenan and alginate represent the compound which important enough in industry. A lot of research proving that seaweed is substance of food which important, like some among other thing is anticancer, antioxidant, preventing cardiovascular, and as diet food. As for content of chemistry compound anticipated by a sharing to cause the effect is compound polyphenol. Referring to above the mentioned, and to know furthermore hit the content polyphenol in Eucheuma sp seaweed, is hence done by analysis research polyphenol in Eucheuma sp seaweed. This research benefit is to give the erudite evidence and information about existence of content polyphenol of Eucheuma sp seaweed. This research is done by using method of spectrofotometric UV-Visible and as reagent used by Folin Ciocalteu and Na2CO3 yield the blue colour, then read by absorbance at 670 nm. As standard condensation used by acid tannat with the concentration 0,25; 0,5; 1,0; 2,0; 4,0; and 8,0 ppm. From research result indicate that the Eucheuma sp seaweed contain the polyphenol with the rate polyphenol of Eucheuma sp I as much 0,054 mg/100g and Eucheuma sp II as much 0,053 mg/100g.Key Words :  Polifenol, Euchema sp and Spectrofotometri UV-Vis.